Some Challenges on the Brazilian Right to be Forgotten in the Digital Era - De Alencar Jr, Francisco Nelson; Gonçalve, Luciana Helena (Journal of Advance Research in Applied Science (ISSN 2208-2352), 2017)
This paper is about the right to be forgotten in the digital age. It aims to present some observations on the right to be forgotten in the digital era, in other words, a right of a person to delist an URL – Uniform Resource Locator - which causes him/her prejudice from the index of search engines, for instance, Google. We believe that the right to privacy has a new calling in the digital era, and, here, especially before search engines. In this way, the right to be forgotten in the digital era can represent an expansion of the protection of the right to privacy. As we will discuss, we believe that observations and the experience of the United States, for example, through the protection of the freedom of expression, and the combat of bad speech with more speech can help the Brazilian legal system to consider a practical way of protection of the privacy sphere on the internet.